Pembuatan Aplikasi CRM Berbasis Web Pada CV. RPM - Michael Steven Magaline; Djoni Haryadi Setiabudi; Rudy Adipranata (Jurnal Infra, 2016)
CV. RPM is one of the authorized dealer of Yamaha motorcycles, located in the town of Luwuk, Central Sulawesi and has been operating since 2009. The products are sold CV. RPM is a motorcycle, parts, service services, and motorcycle accessories and merchandise for the brand Yamaha. CV. RPM has three branches dealer who can service sales of motorcycles.CV. RPM has used the information system to help the company's operational activities such as accounting, stock management, sales, and purchases. In the sales process, information systems used to assist in making consumer data recording, the recording of information products, manufacturing sales order, and the making of a delivery order. For the accounting division, information systems assist in the leasing party billing, which is the guarantor agency when consumers purchases motorcycle with installment, do the bookkeeping, managing billing companies, and financial reports. The result of this research is able to make a CRM application that can record customer’s complaints, create questionnaire, record transaction data, sales force automation application, marketing campaign application, and inventory.